Tropism of subgroup J avian leukosis virus as detected by in situ hybridization - Arshad, S. S.; Smith, L. M.; Howes, K.; Russell, P. H.; Venugopal, K.; Payne, L. N. (Taylor and Francis Group, 1999)
The HPRS-103 strain of avian retrovirus is the prototype of subgroup J avian leukosis virus (ALV-J) and causes myeloid leukosis in meat-type chickens. Using immunohistochemical detection of the viral group-specific antigen (Gag) we have previously demonstrated that the induction of myeloid leukosis by ALV-J is associated with viral tropism for myelomonocytic cells. In this paper we describe an in situ hybridization (ISH) technique using digoxigenin (DIG)-labelled probes for detecting RNA transcripts in tissues from chickens infected with avian leukosis viruses (ALV) of subgroups J (HPRS-103 strain) and A (RAV-1 strain). Virus-specific RNA was detected mainly in the heart, kidney, proventriculus and adrenal in locations similar to those of the Gag protein. Viral gene expression could not be detected in the bone marrow or tumour tissues using this test. Higher levels of viral gene expression in the bursa of Fabricius infected with RAV-1, but not with HPRS-103, might help explain the inability of the latter virus to induce lymphoid leukosis.